Kadar Homosistein Plasma Berhubungan dengan Derajat Keparahan Stroke Iskemik Akut - Bintang, Andi Kurnia (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2022)
Introduction: Stroke is a major health problem globally, as well as Indonesia. It has high mortality and morbidity rate. Most patients have disability that impacts their quality of life. Recent studies reported the role of homocysteine in neurotoxicity, disruption of the blood-brain barrier, and oxidative stress. However, evidences regarding stroke severity and clinical outcome are still not consistent. Aim: Analyze correlation between serum homocysteine levels and severity index and clinical outcome the acute ischemic stroke. Methods: Subjects in this cross-sectional study were first-attack acute ischemic stroke patients with an onset less than 96 hours were recruited. Venous blood was collected within the first 24 hours of admission for serum homocysteine measurement. Severity index was assessed with National Institute of Health Stroke Scale (NIHSS) score. Clinical outcome was determined using the modified Rankin scale (mRS) score on the 14th day after stroke onset. Spearman’s coefficient was used to analyze correlation. Results: As many as 52 subjects were recruited, with female predominance (n=28, 53,8%). Serum homocysteine levels were higher in males (p=0,006) and had positive correlation with NIHSS score (r=0,029, p=0,036). No correlation was observed with mRS score (r=0,17, p=0,24). Subgroup analysis on homocysteine <15µmol/L showed correlation with stroke severity index (r=0,35, p=0,01). Discussion: This study supports previous ones regarding correlation between serum homocysteine levels and severity index in acute phase of ischemic stroke. No correlation was observed between serum homocysteine level and early clinical outcome. Correlation was found at serum homocysteine levels <15µmol/L. Keywords: acute ischemic stroke, homocysteine, NIHSS